Pre-fracture individual characteristics associated with high total health care costs after hip fracture. Issue 3 (March 2017) - Schousboe, J.; Paudel, M.; Taylor, B.; Kats, A.; Virnig, B.; Dowd, B.; Langsetmo, L.; Ensrud, K.
Abstract Summary Older women with pre-fracture slow walk speed, high body mass index, and/or a high level of multimorbidity have significantly higher health care costs after hip fracture compared to those without those characteristics. Studies to investigate if targeted health care interventions for these individuals can reduce hip fracture costs are warranted. Introduction The aim of this study is to estimate the associations of individual pre-fracture characteristics with total health care costs after hip fracture, using Study of Osteoporotic Fractures (SOF) cohort data linked to Medicare claims. Methods Our study population was 738 women age 70 and older enrolled in Medicare Fee for Service (FFS) who experienced an incident hip fracture between January 1, 1992 and December 31, 2009. We assessed pre-fracture individual characteristics at SOF study visits and estimated costs of hospitalizations, skilled nursing facility and inpatient rehabilitation stays, home health care visits, and outpatient utilization from Medicare FFS claims. We used generalized linear models to estimate the associations of predictor variables with total health care costs (2010 US dollars) after hip fracture. Results Median total health care costs for 1 year after hip fracture were $35, 536 (inter-quartile range $24, 830 to $50, 903). Multivariable-adjusted total health care costs for 1 year after hip fracture were 14 % higher ($5256, 95 % CI $156 to $10, 356) in those with walk speed <0.6 m/s compared to ≥1.0 m/s, 25 % higher ($9601, 95 % CI $3314 to $16, 069) in those with body mass index ≥30 kg/m2 compared to 20 to 24.9 mg/kg2, and 21 % higher ($7936, 95 % CI $346 to $15, 526) for those with seven or more compared to no comorbid medical conditions. Conclusions Pre-fracture poor mobility, obesity, and multiple comorbidities are associated with higher total health care costs after hip fracture in older women. Studies to investigate if targeted health care interventions for these individuals can reduce the costs of hip fractures are warranted.